Goals and Action Plans Across Time and Place—A Qualitative Study Exploring the Importance of “Context” in Person-Centered Rehabilitation - Eggen, Linda; Thuesen, Jette (Frontiers in Rehabilitation Sciences, 2022)
ABSTRACT Background: Person-centredness is increasingly addressed in relation to rehabilitation interventions. Collaborative goal setting and action plans are key measures in person-centred rehabilitation. There is a lack of knowledge about how person-centred goals and action plans developed away from the patient’s everyday life are experienced by patients after discharge. Purpose: This aim of the study is to explore how patients with rheumatic diseases experience the relevance of goals and action plans after discharge from inpatient rehabilitation hospital stay. Methods: Individual narrative interviews were conducted with eight patients with rheumatic diseases, aged between 40 and 60. A convenience sampling strategy was applied. Data collection, analysis and interpretation of data were performed within a phenomenological-hermeneutic framework inspired by Paul Ricoeur’s interpretative philosophy. Results: The analysis derived one core theme, “The relevance of goals and action plans is contextual” and three subthemes: "Admission – a protected bubble", "Back home - a harsh reality", and "Need for post-discharge support". Conclusion: This study indicates that the relevance of goals and action plans to patients with rheumatic diseases is context specific. On the basis of the study, it is suggested that the context should be considered in rehabilitation practice, including the social network of the patients. This is in order to support patients in rehabilitation interventions to manage everyday life with disease after discharge to their own homes. Moreover, the concept of context in person-centred rehabilitation should be reconsidered. The study also concludes that there is a need for further development and research in follow up programs, as it is not clear what may constitute an optimal design of follow up support.